Properties of magnesium silicate hydrate (M-S-H) cement mortars containing chicken feather fibres. (20th August 2018) - Zhang, Tingting; Dieckmann, Elena; Song, Shizhuo; Xie, Jingyi; Yu, Zewei; Cheeseman, Christopher
Highlights: Chicken feather fibres reinforced magnesium silicate hydrate (M-S-H) cement mortars. The fibres very effectively bond into M-S-H cement mortars. M-S-H cement mortar has significantly lower pH than Portland cement mortar. Optimal feather fibre addition based on processing and properties was 4 wt%. Abstract: Fibres derived from waste chicken feathers have been used to reinforce magnesium silicate hydrate (M-S-H) cement mortars and Portland cement mortars using up to 5% of fibres by weight of dry binder. The properties of the feather fibre mortar composites including pH, density, flexural strength, compressive strength, toughness, thermal conductivity and microstructure are reported. Feather fibres bond very effectively into M-S-H cement mortars which has significantly lower pH (∼10.8) than Portland cement mortars (pH ∼ 12.6). Increasing the feather fibre content reduces the density, compressive strength, bending strength and thermal conductivity of samples but increases mortar toughness. The optimal feather fibre addition was determined to be 4 wt% by weight of dry binder content, based on ease of mixing the samples and the strength, toughness and thermal conductivity data. Potential applications for feather fibre reinforced M-S-H cement mortars boards are discussed.